Bound by barriers: demystifying the constraints on an elevated Kuwait-Turkiye co-operation in the defence realm - Bakir, Ali; Koc, Engin (Routledge Journals, Taylor & Francis Ltd, 2025)
In the past decade, several Gulf Cooperation Council (GCC) states have diversified their defence partnerships and intensified local defence-industry initiatives, increasingly considering T & uuml;rkiye as a viable option. However, Kuwait's position differs from that of its Gulf counterparts in three key ways. First, Kuwait is less inclined to enhance its security and defence ties with T & uuml;rkiye compared to the UAE, Qatar, and Saudi Arabia. Second, unlike these nations, Kuwait shows little interest in developing a domestic defence industry. Third, although there have been recent positive developments in Kuwaiti-Turkish defence relations, these ties remain limited compared to the robust political and economic connections between the two countries and the extensive defence relationships other GCC states have cultivated with T & uuml;rkiye. To address the question of why, our paper draws on small state theories, utilizing a mixed-methods approach that includes interviews and communications with officials and experts, as well as analysis of primary sources.
Keywords: Kuwait-T & uuml;rkiye relations; Kuwait's defence industry; Gulf security; small state theory; Shelter strategy; Kuwait-Turkiye defence ties